Serum Total Bilirubin With Hospital Survival in Adults During Extracorporeal Membrane Oxygenation - Huang, Rui; Shao, Min; Zhang, Cheng; Fang, Ming; Jin, Mengmeng; Han, Xuan; Liu, Nian (Frontiers in Medicine, 2022)
Background Extracorporeal membrane oxygenation (ECMO) is widely used for refractory cardiopulmonary failure treatment. The disadvantage of ECMO is its higher risk profile and clinical resource consumption. This observation examines the role of serum total bilirubin (TBIL) as a predictor of adult patient outcomes on ECMO support. Methods This retrospective observation reports a single-center experience with adults on ECMO support between 2018 and 2021. Data were collected regarding demographics, ECMO details, laboratory parameters, and outcomes. We examined the elevation of TBIL to predict survival and variables associated with hyperbilirubinemia. Results The patients who died within 28 days had a 2-fold higher peak level of TBIL than those who survived (73.10 [38.60, 98.64 vs. 34.50 [24.03, 54.85]; P = 0.003). Univariate logistic regression analyses demonstrated that high TBIL was remarkably associated with an elevated risk of 28-day mortality (OR: 7.25; 95% CI: 2.31~25.49; P = 0.001) and total mortality (OR: 5.71; 95% CI: 1.82~20.66; P = 0.001). The TBIL value was 65 μmol/L as the best cut-off value, and the observation group was divided into a high TBIL subgroup (n = 21) or a low TBIL subgroup (n = 39). The demographic and clinical features did not show a difference, whereas SOFA and APACHE II scores and ALT, AST and LAC before ECMO initiation correlated with high or low TBIL (P < 0.05). For coagulation function at the time of TBIL peak, the levels of PT, APTT, PTA and FIB were different between the two subgroups (P < 0.05). The SOFA score was potentially associated with hyperbilirubinemia after ECMO initiation, and the prediction accuracy was 0.800. Conclusion Serum total bilirubin elevation appears after ECMO initiation and correlates with survival, while other markers of liver injury do not. Serum total bilirubin is an easy-to-measure biomarker to be a predictor of survival after ECMO initiation.